1990
DOI: 10.1080/02640419008732129
|View full text |Cite
|
Sign up to set email alerts
|

Peak treadmill running velocity during theVO2max test predicts running performance

Abstract: Twenty specialist marathon runners and 23 specialist ultra-marathon runners underwent maximal exercise testing to determine the relative value of maximum oxygen consumption (VO2max), peak treadmill running velocity, running velocity at the lactate turnpoint, VO2 at 16 km h-1, % VO2max at 16 km h-1, and running time in other races, for predicting performance in races of 10-90 km. Race time at 10 or 21.1 km was the best predictor of performance at 42.2 km in specialist marathon runners and at 42.2 and 90 km in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
248
1
12

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(294 citation statements)
references
References 24 publications
33
248
1
12
Order By: Relevance
“…Foi utilizada esta concentração, e não 4mM, em função da duração do estágio (3min). A maior velocidade atingida durante o teste e mantida por pelo menos 1 minuto foi considerada como a velocidade aeró-bia máxima (Vamax) 16 . …”
Section: Futebol De Paralisados Cerebralunclassified
“…Foi utilizada esta concentração, e não 4mM, em função da duração do estágio (3min). A maior velocidade atingida durante o teste e mantida por pelo menos 1 minuto foi considerada como a velocidade aeró-bia máxima (Vamax) 16 . …”
Section: Futebol De Paralisados Cerebralunclassified
“…20 e maximum aerobic velocity (MAV) predicts running performance of middle and long distance athletes [1][2] . Moreover, it can be used in the control and prescription of exercise training 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the protocol selection can in uence this measure [10][11] . N et al 2 demonstrated that the S et al 7 method, based on peak velocity (V peak ), performed with an incremental protocol on a treadmill, is capable to predict runners' performance in long distance races (10 to 90 km). Additionally, the authors suggested that muscular factors related to power capacity, and not the cardiovascular system, limited this variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest velocity reached during a complete stage in the test was recorded as the velocity peak (VP) (15) . The HR max was determined as the highest value recorded at the end of the last stage of the incremental test.…”
Section: Incremental Testmentioning
confidence: 99%